Problems and Prospects of Soybean Production in Bangladesh (Annals of Bangladesh Agriculture, 2022)
A study was conducted to assess the challenges and prospects of soybean production in Bangladesh. Data were collected from 55 soybean-growing farmers of 5 districts through interview and focus group discussions (FGDs). The data indicated that there are great opportunities to expand soybean production areas due to high profitability, availability of suitable land, mechanized management practices, the comparative advantage and interest of farmers in soybean cultivation. The challenges of soybean production include better suited soybean varieties between boro and amon rice, the incidence of insects, climatic variability, publicity for soybean production, unwillingness of industrialists, soybean oil extraction facilities, attack of diseases, instable market price and network, fund and technical knowledge. Ultimately, result indicated that the opportunities of soybean production outweigh than challenges in Bangladesh. Such results could also contribute to increase soybean production in Bangladesh.Ann. Bangladesh Agric. (2021) 25 (2) : 97-104